2010
DOI: 10.1523/jneurosci.2709-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on a Retinophilin/Myosin Complex for Stability of PKC and INAD and Termination of Phototransduction

Abstract: Normal termination of signaling is essential to reset signaling cascades, especially those such as phototransduction that are turned on and off with great rapidity. Genetic approaches in Drosophila led to the identification of several proteins required for termination, including protein kinase C (PKC), NINAC (neither inactivation nor afterpotential C) p174, which consists of fused protein kinase and myosin domains, and a PDZ (postsynaptic density-95/Discs Large/zona occludens-1) scaffold protein, INAD (inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…From this collection we identified the MORN family member retinophilin ( rtp , also called undertaker ( uta )). Retinophilin participates in termination of phototransduction in the fly retina (Mecklenburg et al, 2010; Venkatachalam et al, 2010) and in store-operated calcium release and phagocytosis in fly embryonic macrophages (Cuttell et al, 2008). It contains four MORN repeats, regions that can bind to phospholipid membranes (Ma et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this collection we identified the MORN family member retinophilin ( rtp , also called undertaker ( uta )). Retinophilin participates in termination of phototransduction in the fly retina (Mecklenburg et al, 2010; Venkatachalam et al, 2010) and in store-operated calcium release and phagocytosis in fly embryonic macrophages (Cuttell et al, 2008). It contains four MORN repeats, regions that can bind to phospholipid membranes (Ma et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The RNAi protection is quantitatively modest, but consistent (Figure 5B). To test whether loss of Retinophilin is responsible for this phenotype, we generated a transheterozygote between two previously characterized loss-of-function mutant alleles of rtp (Mecklenburg et al, 2010; Venkatachalam et al, 2010). Axons in this rtp mutant are preserved following taxol treatment (Figure 5C and D), confirming that removal of retinophilin is indeed axoprotective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that ninaC peaks later in the night than inaD, stops, and norpA, but similar to the time of peaking of another gene encoding a retinophilin (RTP) (AGAP003547). In Drosophila, NINAC and RTP are binding partners, and their protein levels are codependent (87). We find in An.…”
mentioning
confidence: 77%
“…aegypti noted apparent dramatic diel changes in rhabdom volume (88). These changes might be driven by the circadian system through both NINAC and RTP, which are both required for normal rhabdomere volume in Drosophila (87,89). Many of these visual system genes continue to be rhythmic in DD conditions, suggesting that components of visual transduction are under circadian clock control (Fig.…”
mentioning
confidence: 99%